Why do you attract me but not others? Retrieval of person knowledge and its generalization bring diverse judgments of facial attractiveness. (2nd September 2020) - Han, Shangfeng; Liu, Shen; Li, Yue; Li, Wanyue; Wang, Xiujuan; Gan, Yetong; Xu, Qiang; Zhang, Lin
ABSTRACT: Judgments of facial attractiveness play an important role in social interactions. However, it still remains unclear why these judgments are malleable. The present study aimed to understand whether the retrieval of person knowledge leads to different judgments of attractiveness of the same face. Event-related potentials and learning-recognition tasks were used to investigate the effects of person knowledge on facial attractiveness. The results showed that compared with familiar faces that were matched with negative person knowledge, those matched with positive person knowledge were evaluated as more attractive and evoked a larger early posterior negativity (EPN) and late positive complex (LPC). Additionally, positive similar faces had the same behavioral results and evoked large LPC, while unfamiliar faces did not have any significant effects. These results indicate that the effect of person knowledge on facial attractiveness occurs from early to late stage of facial attractiveness processing, and this effect could be generalized based on the similarity of the face structure, which occurred at the late stage. This mechanism may explain why individuals form different judgments of facial attractiveness.